2007
DOI: 10.1007/s11852-007-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-based vulnerability assessment of coastal natural hazards, state of Pará, Brazil

Abstract: Studies carried out in the NE coastal zone of the State of Pará (Brazil) have recorded, in the last 25 years, numerous evidence of natural impacts of the flood and erosion processes. As a consequence, diverse strategies and measures of population adaptation have been implemented but with limited success. Therefore, in order to subsidize the Coastal Zone Management Program of Pará, this paper aims to identify, assess and classify natural and socioeconomic vulnerabilities of this coastal zone by means of a Geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(67 citation statements)
references
References 15 publications
(9 reference statements)
1
54
0
7
Order By: Relevance
“…Dawson et al (2009) also contested that probabilistic methods should be adopted to predict coastal erosion. Indeed for a given model, the validity of the result depends on many factors (Szlafsztein and Sterr, 2007). It is the reason why the scenario generator and the visualization toolkit are involved in the DSF in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dawson et al (2009) also contested that probabilistic methods should be adopted to predict coastal erosion. Indeed for a given model, the validity of the result depends on many factors (Szlafsztein and Sterr, 2007). It is the reason why the scenario generator and the visualization toolkit are involved in the DSF in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…And most of the existing decision support related to coastal erosion was potentially underlain by the complete physical, socioeconomic datasets and the deterministic solutions. In fact, in many developing countries it is usually possible that some key parameters affecting model output are unavailable (Szlafsztein and Sterr, 2007), and the relevant research is still inadequate. In the case of Yangtze Delta, most current published studies about coastal erosion were focused on the causes and types of erosion (Cai et al, 2009;Chen et al, 1988;Gao and Wang, 2008;Hori et al, 2002;Milliman et al, 1985;Yang et al, 2001Yang et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the respondents (19/22) indicated that a Web-based application would be ideal for navigating the database and for consulting the cartographic information. Much effort has gone into developing such tools for natural hazard management and prevention in recent years in order to facilitate the elaboration of emergency evacuation plans (Chakraborty et al 2005;Szlafsztein & Sterr 2007;Tate et al 2010;Le Cozannet et al 2014) or as a means of risk visualization and communication (Brown et al 2006). This option would also allow data to be updated from a single source.…”
Section: Diffusion and Implementation Of The Toolmentioning
confidence: 99%
“…Thus, several approaches of geo-environmental fragility/ vulnerability evaluation that used GIS and remote sensing were developed over the last few years (e.g. Szlafsztein and Sterr 2007, Pandey et al 2008, Anfuso and Del Pozo 2009, Andrade et al 2010, Fernandes-da-Silva et al 2010, Ifeanyi et al 2010, Fernández and Lutz 2010 45'W ( Figure 1). In addition, we chose the study area due to the occurrence of several landscape units with different geological and geomorphological characteristics for application of the methodology, ranging from mountain escarpment areas in the Crystalline Basin to stretches of the alluvial plains of the Paraíba do Sul river, inserted in the Sedimentary Basin of Taubaté.…”
Section: Introductionmentioning
confidence: 99%